2012
DOI: 10.1103/physrevb.86.184109
|View full text |Cite
|
Sign up to set email alerts
|

Aging and deaging effects in shape memory alloys

Abstract: Physical properties in shape memory alloys are known to change as a result of aging over time. However, undesired aging effects in the martensite phase can be eliminated once the aged martensite is brought into the parent phase, often referred to as deaging. We propose a Landau free energy model to study the aging and deaging of martensite. These two effects can be modeled via the increase and decrease of an internal field which adopts the same "symmetry" as the crystal symmetry of the host lattice. Time depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…The in situ time-dependent XRD profiles for BNT–5BT at 70 °C (figure 7(c) inset) shows that the gradual development of long-range ordering domains, especially in the initial 2 h, were consistent with the time period of the modulus valleys. After the ‘stepwise increase’, the modulus becomes saturated with time evolution, indicating that the isothermal transition is nearly complete and an ageing effect becomes dominant [5053]. …”
Section: Resultsmentioning
confidence: 99%
“…The in situ time-dependent XRD profiles for BNT–5BT at 70 °C (figure 7(c) inset) shows that the gradual development of long-range ordering domains, especially in the initial 2 h, were consistent with the time period of the modulus valleys. After the ‘stepwise increase’, the modulus becomes saturated with time evolution, indicating that the isothermal transition is nearly complete and an ageing effect becomes dominant [5053]. …”
Section: Resultsmentioning
confidence: 99%
“…For instance, three nonlinear oscillators mutually coupled to each other were used as a source of entangled W states [29]. It is particularly important because recently, tri and multipartite entanglement becomes one of the most intriguing features discussed in the literature (for instance see [15,30]).…”
Section: Introductionmentioning
confidence: 99%
“…* sbougouffa@hotmail.com A number of theoretical and experiments studies were carried out on the simplest quantum network composed of only two cavities, and several schemes have been proposed in which an efficient transmission between the cavities could be achieved [16][17][18]. In most treatments the cavities contained two-level atoms, and the creation of entanglement between the atoms and its transfer to the cavity modes was considered [19][20][21][22][23][24][25][26][27][28][29][30]. It has also been demonstrated that effective quantum gates between atoms located in distant cavities can be realized even in the presence of losses and imperfections in coupling strengths [31,32].…”
Section: Introductionmentioning
confidence: 99%